2004
DOI: 10.1375/1369052042335331
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Inhibition as a Function of Relationship in Preschool Twins and Siblings

Abstract: M onozygotic (MZ) twins spend more time with each other and are more genetically alike than are dizygotic (DZ) twins or nontwin siblings and therefore probably experience less diversity in their playmates than DZ twins, who in turn may experience less diversity than other-age siblings. Thus MZ twins may be more inhibited than DZ twins, who may in turn be more inhibited than nontwin siblings. To test this, 205 children (42 MZ twins, 94 DZ twins, and 69 nontwin siblings) were assessed in a playroom laboratory du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…In line with previous research (DiLalla & Caraway, 2004) the current study found mean differences across measures of sibling relationship between MZ and DZ pairs. However, in regard to the question concerning patterns of association between measures of sibling relationship and behavioral outcome our findings indicate no significant differences.…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous research (DiLalla & Caraway, 2004) the current study found mean differences across measures of sibling relationship between MZ and DZ pairs. However, in regard to the question concerning patterns of association between measures of sibling relationship and behavioral outcome our findings indicate no significant differences.…”
Section: Discussionsupporting
confidence: 92%
“…However, it is important to note that the longitudinal design of the present study brings us one step closer to testing the alternative hypotheses directly by allowing examination of the directionality of the association. Additionally, the present study examined a general population sample of same-sex twins, and prior studies have reported that twins have higher incidence of language delay than singletons at early ages (e.g., Rutter et al, 2003; Thorpe, 2008) and are more behaviorally inhibited compared to singletons in a preschool sample (DiLalla & Caraway, 2004). If these mean differences between twins and singletons are accompanied by differences in how behavioral inhibition and language relate to each other, it will be important to replicate the results in other samples to determine generalizability.…”
Section: Discussionmentioning
confidence: 97%
“…Also, we examined two different measures of behavioral inhibition (observed and parent-reported), which have been shown to be significantly associated but distinct in an earlier study using the present sample (Smith et al, 2012). Some of the associations between behavioral inhibition and language development were limited to parent-reported behavioral inhibition, which may reflect the rater-driven differences specific to parent-reported behavioral inhibition (e.g., DiLalla & Caraway, 2004); for example, parents have a larger sampling of behavioral observations on which to rate their children’s behavior, and likely use different reference points for comparisons (e.g., other children in their family). We also had multiple measures of observed and parent-reported behavioral inhibition, which reduced measurement error and led to a more reliable assessment.…”
Section: Discussionmentioning
confidence: 99%
“…In a large twin-singleton comparison study (Pulkkinen et al 2003), 12-year-old twins were reported to be more socially adaptable than non-twins, but no twin-singleton differences were found for social anxiety. A twinsingleton comparison of both maternal CBCL withdrawn ratings and laboratory assessment of inhibition in 5-yearolds yielded inconsistent results (DiLalla and Caraway 2004). According to laboratory ratings, twins were more inhibited than non-twins, whilst maternal ratings showed the opposite.…”
Section: Discussionmentioning
confidence: 99%